Creating a Space for Mathematicians and Educators: The philosophical basis for the Klein Project - Barton, Bill (2014)
The Klein Project is unique within contemporary initiatives in mathematics education because it is deliberately designed to use the potential of both mathematicians and mathematics educators to enhance the quality of teaching at the upper levels of secondary school. This means that a "space" must be created where productive discussions can be held, free from the divisions, pre-conceptions, and acrimony that has characterised some interactions between these two groups. It also means that there must be a mechanism for all those interested to make a significant contribution. I discuss how this is achieved.